Ventilatory Disorders - Pokorski, Mieczyslaw (Neuroscience and Respiration ;, 2015)
Respiratory function is a major determinant of the overall quality of health and well-being of an individual. This book runs the gamut of chapters devoted to chronic cough-related conditions in children and adults, health care quality and safety, environmental pollution health effects, efficiency of therapeutic approaches, and a mutual dependence of respiratory and non-respiratory illnesses. An integrated approach to the investigation and treatment of sleep disordered breathing as well as the use of new and more efficient diagnostic strategies for pleural tuberculosis are presented. Chapters focus on translating science into practice, with an eye on presymptomatic identification of serious ailments for which there could be more effective therapy, leading to improved general health outcomes. This book includes chapters about disorders which will be of interest to clinicians, family practitioners, and medical researchers.